JUMLAH KOLONI CANDIDA ALBICANS PADA PLAT RESIN AKRILIK HEAT CURED SETELAH DILAKUKAN PERENDAMAN EKSTRAK DAUN KEMANGI (OCIMUM BASSILICUM LINN) 50% - Ayu Wirayuni, Kadek; Nugrahini, Sintha (Interdental: Jurnal Kedokteran Gigi, 2020)
Accumulation of plaque and food scraps on an acrylic resin base will increase bacterial colonies and C. albicans which will cause denture stomatitis. Maintenance of denture hygiene using mechanical, chemical and combination of two methods. Basil leaf extract contain essential oils which are important in fight against resistant C. albicans biofilms. The purpose of this study was to determine the comparison of C. albicans colonies after cleaning various denture cleaning methods. The method of this study is used an experimental method, the study design is posttest only with control group design. Sample size of heat-cured acrylic resin plate is 40x12x3mm. this study use Kruskall-Wallis test and Mann-Whitney test as data analysis for comparison tests between groups (non-parametric test). The results showed that there were significant differences between the various cleansing methods used in reducing C. albicans colonies. The compotition of flavonoids basil leaf extract is anti-microbial which can prevent the entry of fungi that harm the body.